2009
DOI: 10.1158/0008-5472.can-08-3240
|View full text |Cite
|
Sign up to set email alerts
|

Akt Activation Synergizes with Trp53 Loss in Oral Epithelium to Produce a Novel Mouse Model for Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a common human neoplasia with poor prognosis and survival that frequently displays Akt overactivation. Here we show that mice displaying constitutive Akt activity (myrAkt) in combination with Trp53 loss in stratified epithelia develop oral cavity tumors that phenocopy human HNSCC. The myrAkt mice develop oral lesions, making it a possible model of human oral dysplasia. The malignant conversion of these lesions, which is hampered due to the induction of premature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 44 publications
4
45
0
1
Order By: Relevance
“…Similar to human SCC, these tumors also expressed robust levels of EGFR and cyclin D1 proteins (Supplemental Figure 1A; supplemental material available online with this article; doi:10.1172/JCI68899DS1), and resemble the recently described "classical SCC" that develops in carcinogentreated mice (27). Human SCCs frequently harbor inactivating mutations in p53 (2,3,28), and p53 inactivation is important for SCC progression in genetic models of oral SCC, cooperating potently with events such as AKT activation (29). Consistent with these data, we found that SCC tumors arising in DMBAtreated p53 +/-mice appeared at reduced latency compared with those occurring in WT mice ( Figure 1C) (30,31).…”
Section: Introductionmentioning
confidence: 68%
“…Similar to human SCC, these tumors also expressed robust levels of EGFR and cyclin D1 proteins (Supplemental Figure 1A; supplemental material available online with this article; doi:10.1172/JCI68899DS1), and resemble the recently described "classical SCC" that develops in carcinogentreated mice (27). Human SCCs frequently harbor inactivating mutations in p53 (2,3,28), and p53 inactivation is important for SCC progression in genetic models of oral SCC, cooperating potently with events such as AKT activation (29). Consistent with these data, we found that SCC tumors arising in DMBAtreated p53 +/-mice appeared at reduced latency compared with those occurring in WT mice ( Figure 1C) (30,31).…”
Section: Introductionmentioning
confidence: 68%
“…Akt-induced senescence has been associated with the activation of TP53-dependent mechanisms (Chen et al ., 2005; Kim et al ., 2007). The results from a previous study suggested that TP53-mediated senescence was responsible for the reduced malignant conversion of oral lesions in mice displaying constitutive Akt activity (myrAkt) (Moral et al ., 2009). While the Western blot results revealed that TP53 was undetectable in association with increased p-Akt, we did detect an increase in the expression of the CDKN2D (p19Arf) gene.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of AKT is one of the major mechanisms of tumorigenesis, and blocking this signaling pathway could have therapeutic implications for tumors. Previous studies demonstrated that the activation of AKT is associated with intrinsic radioresistance, tumor cell proliferation, and angiogenesis in vivo [27]. AKT can affect proliferation signaling and induce anti-apoptotic effects in tumors.…”
Section: Discussionmentioning
confidence: 99%